Pharmacokinetics of plasma infusion in congenital thrombotic thrombocytopenic purpura. (31st December 2018) - Taylor, A.; Vendramin, C.; Oosterholt, S.; Della Pasqua, O.; Scully, M.
Abstract : Essentials Congenital thrombotic thrombocytopenic purpura (TTP) is primarily treated with plasma infusion. We present a pharmacokinetic analysis of ADAMTS‐13 in six patients following plasma infusion. A median half‐life of 130 h was demonstrated, ranging between 82.6 and 189.5 h. Investigation of interindividual clearance of ADAMTS‐13 is necessary to optimize treatment. Summary: Background: Congenital thrombotic thrombocytopenic purpura (TTP) is defined by persistent severe deficiency of ADAMTS‐13 in the absence of anti‐ADAMTS‐13 inhibitory antibodies, confirmed by mutational analysis. Replacement of the missing protease prevents disease relapse, primarily using plasma infusion (PI). Objectives, patients and methods: There is scant evidence regarding optimal dose and frequency of treatment, which tends to be empirically guided. We present a pharmacokinetic analysis of ADAMTS‐13 in six patients with congenital TTP on established regimes following PI. Results: We found a median clearance of 25.41 mL h −1 and half‐life of 130 h, ranging between 82.6 and 189.5 h (3.4–7.9 days, respectively). All patients reached baseline ADAMTS‐13 level within 7–10 days post‐plasma. Median ADAMTS‐13 activity peak post‐PI was 24.05 IU dL −1 . Variation was related to elimination rate, which, in turn, was affected by weight and metabolism, but not to von Willebrand factor antigen or activity levels. Using the pharmacokinetic parameters, we simulated individualized protocols based on PI dose or frequency to target hypothetical optimal plasma levels of ADAMTS‐13 of 10 and 50 IU dL −1, respectively. Results suggest a target trough ADAMTS‐13 of 10 IU dL −1 is feasible but 50 IU dL −1 would not be achievable taking into account volume required. Conclusions: Further work is needed to compare treatment of congenital TTP with PI vs. recombinant ADAMTS‐13. PI may provide longer duration of ADAMTS‐13 effect, but is limited by plasma volume required, whereas recombinant therapy can provide a higher ADAMTS‐13 peak. We propose that investigation of interindividual clearance of ADAMTS‐13 is necessary to optimize treatment and provide the rationale for dose and frequency of prophylaxis.